Calboxyvinyl polymer adjuvant enhances respiratory IgA responses through mucosal and systemic administration - Eita Sasaki; Hideki Asanuma; Haruka Momose; Jun–ichi Maeyama; Saya Moriyama; Noriyo Nagata; Tadaki Suzuki; Isao Hamaguchi; Hideki Hasegawa; Yoshimasa Takahashi (npj Vaccines)
Abstract Adjuvants play a crucial role in enhancing vaccine efficacy. Although several adjuvants have been approved, there remains a demand for safer and more effective adjuvants for nasal vaccines. Here, we identified calboxyvinyl polymer (CVP) as a superior mucosal vaccine adjuvant from pharmaceutical base materials using our screening systems; single nasal vaccination of the CVP-combined influenza split vaccine-induced antigen-specific IgA and IgG antibodies and provided protection against lethal influenza virus infection. Furthermore, nasal vaccination with CVP-combined severe acute respiratory syndrome coronavirus 2 antigen protected against the virus and stimulated the production of highly cross-reactive IgG antibodies against variants XBB1.5 and JN.1. Intriguingly, intramuscular vaccination of the CVP-combined vaccine also elicited the production of IgA antibodies in both nasal wash and bronchoalveolar lavage fluid in mice and cynomolgus monkeys. CVP therefore offers superior adjuvanticity to existing adjuvants and is anticipated to be a safe and effective adjuvant for mucosal vaccines.